Prospects of development of network interaction of universities in training for the sphere of advertising and public relations - E. V. Moreeva (Путеводитель предпринимателя)
Network interaction of educational organizations provided by the Law «On education in the Russian Federation» is most effectively implemented in the process of cooperation of universities in theframework ofdistance learning programs. Thus, in particular, networking in the training of specialists in the field ofadvertising and public relations on the basis of a unified distance learning program possible on the basis of a number of Moscow universities: Russian state University for the Humanities, national research University «Moscow power engineering Institute», Moscow financial and law University, Moscow University named S. U. Vitte, etc. The article discusses the conditions for the implementation ofdistance education program by participating universities, as well as the data reflecting the degree of students « satisfaction with the process ofdistance learning.